Comparison of the clinicopathological features of flat and polypoid colorectal adenomas that are smaller than or equal to five millimeters - Neşe Arzu Yener; Ahmet Midi; Çiğdem Ataizi Çelikel (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Colorectal flat adenomas (FAs) may represent a different histogenesis, since their malignant potential is thought to be higher than polypoid adenomas of the same size. In this study, we classified FAs of ≤5 mm into three subgroups-superficially elevated adenomas (SEAs), completely flat adenomas (CFAs), and depressed adenomas (DAs)-based on their low microscopic shapes and compared their clinicopathological features with polypoid tubular adenomas (pTAs) with the same size. Materials and Methods: One hundred one pTAs and 46 FAs with tubular morphology with the same size (≤5 mm) were studied. Results: The percentages of high-grade dysplasia in FAs and pTAs were 19.56% and 12.87%, respectively. The percentages of the high-grade dysplasia were 28.57%, 13.63%, and 20.00% in the DA, SEA, and CFA subgroups, respectively. FAs had a significantly higher number of normal epithelium at the basal crypts of the lesion than the pTAs (p=0.001). The presence of pericryptal mesenchymal cells was higher in pTAs than the FAs (78.21% vs 10.86%) (p<0.001). Conclusion: Flat adenoma represents a distinct type of colorectal adenoma with special histopathological properties-existence of a normal epithelium at the basal crypts, lack of pericryptal mesenchymal cells, and a high percentage of high-grade dysplasia-especially when it has a depressed shape at low magnification. Turkish Başlık: Beş milimetre ve daha küçük flat ve polipoid kolorektal adenomların klinik ve histopatolojik özellikleri açısından karşılaştırılması Anahtar kelimeler: Flat kolorektal adenom, non-polipoid kolorektal neoplazi, kolorektal karsinogenezis, kolorektal adenom, kolorektal adenomatöz polip Arkaplan/Amaç: Kolorektal flat adenomlar, aynı büyüklükteki polipoid adenomlara göre daha yüksek oranda ağır displazi gösterdiklerinden bu lezyonların farklı histogenetik temelleri olduğu düşünülmektedir. Yöntemler ve Gereçler: Deprese (DA), tamamen düz (CFA) ve hafif kabarık (SEA) olarak üç alt grupta incelediğimiz; 5 mm ve daha küçük boyutlardaki 46 adet flat, tübüler kolorektal adenom ile aynı boyutta ve yerleşimde 101 adet polipoid, tübüler kolorektal adenomun histopatolojik ve klinik özellikleri karşılaştırıldı. Bulgular: Yüksek dereceli displazi flat adenomlarda %19.56 iken polipoid adenomlarda %12.87 idi. Bu özellik, DA, SEA ve CFA alt gruplarında sırasıyla %28.57; %13.63 ve %20.00 idi. Flat adenomlarda lezyonun bazalinde yerleşimli kriptlerde normal epitel varlığı, polipoid tubuler adenom grubundan anlamlı olarak fazla idi (p=0.001). Perikriptal mezenkimal hücreler polipoid tubuler adenom grubunda flat adenom grubundan istatistiksel olarak daha fazla idi (p<0.001). Sonuç: Bazal kriptlerde normal epitelin daha fazla görülmesi, perikriptal mezenkimal hücrelerin azalması ve daha yüksek oranda ağır displazi göstermesi açısından, özellikle deprese görünüme sahip flat adenomların polipoid adenomlardan daha farklı bir kolorektal adenom türü olduğu söylenebilir.